JHWH i Jego maṣṣēbâ? Tel Arad i graniczny wyznacznik terytorium pod protektoratem Boga Izraela - Janusz Lemański (Studia Koszalińsko-Kołobrzeskie, 2022)
The article deals with the discovery of a judean temple in Tel Arad (VIII/VII century B.C.). The stele (maṣṣēbâ) found in it allows us to believe, that in the official cult of the monarchy period, such a cult object symbolized YHWH. Bible texts can help to interpret this find. In addition to the official condemnation, prohibition on building and the order to destroy the already existing such cult installations (mainly pagan), you can also find positive references in the biblical texts both in the sphere of worship (mainly in the tradition of Jacob: the stele dedicated to YHWH in Betel; Os 3:4: Kingdom of Israel), as well as purely secular ones (monuments, tomb steleae). However, the location of Tel Arad on the southern border of Judah suggests, that the stele found there could have been a symbolic marker of the border of this country and a sign of protection of its territory on the part of YHWH (cf. Gen 31:45.51–53); Is 19:19).